Removing the Graduate Record Examination as an Admissions Requirement Does Not Impact Student Success - Lisa M. Sullivan; Amanda A. Velez; Nikki Longe; Ann Marie Larese; Sandro Galea (Frontiers Media S.A., 2022)
Background: The predictive validity of components of the Graduate Record Examination (GRE) on student success is inconsistent, and the test itself has been shown to be a barrier for prospective students historically underrepresented in graduate programs.Policy Options and Recommendations: We analyzed three admissions cycles for the Master of Public Health degree at the Boston University School of Public Health before (2016, 2017, 2018) and after (2019, 2020, 2021) eliminating the GRE for diversity and quality of applications, student success, and employment outcomes. We observed increases in diversity (e.g., 7.1% and 7.0% self-identified as African American/Black and Hispanic before eliminating the GRE as compared to 8.5% and 8.2% after), but no loss of quality, as measured by undergraduate grade point averages (GPAs) (e.g., median undergraduate GPA before and after eliminating the GRE of 3.4). We also saw no difference in performance in required core courses (e.g., more than 93.5% of students earned passing grades in required courses before and 94.5% after eliminating the GRE) and graduate employment (i.e., 93.1% employed within 6 months of graduation before and 93.8% after eliminating the GRE). We recommend removing the GRE as an admission requirement for the MPH as a step toward diversifying the public health workforce. This change alone is necessary but insufficient. We also need to develop support programs, tailored specifically to the needs of our future students, to ensure their success.Conclusion: Eliminating the GRE as an admissions requirement for prospective students does not result in loss of student quality or worse program performance.